Acceleration or deceleration of self-motion by the Marangoni effect - Matsuda, Yui; Suematsu, Nobuhiko J.; Kitahata, Hiroyuki; Ikura, Yumihiko S.; Nakata, Satoshi (Chemical physics letters, 2016)
[Display omitted] •The driving force of camphor motion is the difference in the surface tension and Marangoni flow generated by a camphor molecular layer developed from the solid camphor.•The speed of self-motion of a camphor disk was accelerated with an increase in the water depth.•The speed of a camphor boat was decelerated with an increase in the water depth. We investigated the water-depth dependence of the self-motion of a camphor disk and camphor boat. With increasing water depth, the speed of motion of the camphor disk increased, but that of the camphor boat decreased in an annular one-dimensional system. We discussed the difference in the water-depth dependence of the speed of the camphor objects in relation to Marangoni flow. We concluded that Marangoni flow, which became stronger with increasing the water depth, positively and negatively affected the speed of the disk and boat, respectively.